CHARACTERISTICS OF RESOCIALIZATION OF PERSONS SENTENCED TO PENALTIES NOT RELATED TO DEPRIVATION OF FREEDOM - Sysoieva, Viktoriia; Kulaksyz, Tsvetelina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyze some aspects of resocialization of persons sentenced to non-custodial sentences in terms of means of correction and re-socialization of convicts. Research methods: philosophical and legal, comparative, systemic, functional, generalization, methods of analysis, synthesis, abstraction. Results: the means of correction and re-socialization of a certain category of convicts were analyzed and researched, namely those whose punishment is not related to imprisonment; compared and analyzed the application of correctional and re-socialization processes to convicts whose punishment is not related to imprisonment and determined the appropriateness of the use of these concepts in combination, taking into account the specifics of this category of convicts; among the means of correction and re-socialization in accordance with this block of convicts were studied: the regime as one of the main tools in the process of adaptation of the convict in society; the appropriateness of probation in this case; the possibility of implementing socially useful work as one of the elements of effective resocialization; social and educational work as a universal tool that should be used for those sentenced to various types of punishment; public influence as the most influential and effective means of correction and resocialization of convicts whose punishment is not related to imprisonment. Resocialization is a process aimed at restoring the moral, mental and physical condition of a person, his social functions, bringing individual or collective behavior in accordance with generally accepted social rules and legal norms. Resocialization as a system of state measures applied to convicts aims to form in them law-abiding behavior, stimulate their formation in a position of life that meets social norms, by restoring, preserving and developing socially useful properties, relations while serving a sentence and further social adaptation of such persons. It should be carried out on the basis of pedagogy of cooperation, respect for human and civil rights and freedoms. Discussion: the article considers various aspects of adaptation and correction of convicts serving certain types of sentences.